Head‐to‐head comparison of structurally unrelated dipeptidyl peptidase 4 inhibitors in the setting of renal ischemia reperfusion injury. (7th June 2017) - Reichetzeder, Christoph; von Websky, Karoline; Tsuprykov, Oleg; Mohagheghi Samarin, Azadeh; Falke, Luise Gabriele; Dwi Putra, Sulistyo Emantoko; Hasan, Ahmed Abdallah; Antonenko, Viktoriia; Curato, Caterina; Rippmann, Jörg; Klein, Thomas; Hocher, Berthold
Abstract : Background and Purpose: Results regarding protective effects of dipeptidyl peptidase 4 (DPP4) inhibitors in renal ischaemia–reperfusion injury (IRI) are conflicting. Here we have compared structurally unrelated DPP4 inhibitors in a model of renal IRI. Experimental Approach: IRI was induced in uninephrectomized male rats by renal artery clamping for 30 min. The sham group was uninephrectomized but not subjected to IRI. DPP4 inhibitors or vehicle were given p.o. once daily on three consecutive days prior to IRI: linagliptin (1.5 mg·kg −1 ·day −1 ), vildagliptin (8 mg·kg −1 ·day −1 ) and sitagliptin (30 mg·kg −1 ·day −1 ). An additional group received sitagliptin until study end (before IRI: 30 mg·kg −1 ·day −1 ; after IRI: 15 mg·kg −1 ·day −1 ). Key Results: Plasma‐active glucagon‐like peptide type 1 (GLP‐1) increased threefold to fourfold in all DPP4 inhibitor groups 24 h after IRI. Plasma cystatin C, a marker of GFR, peaked 48 h after IRI. Compared with the placebo group, DPP4 inhibition did not reduce increased plasma cystatin C levels. DPP4 inhibitors ameliorated histopathologically assessed tubular damage with varying degrees of drug‐specific efficacies. Renal osteopontin expression was uniformly reduced by all DPP4 inhibitors. IRI‐related increased renal cytokine expression was not decreased by DPP4 inhibition. Renal DPP4 activity at study end was significantly inhibited in the linagliptin group, but only numerically reduced in the prolonged/dose‐adjusted sitagliptin group. Active GLP‐1 plasma levels at study end were increased only in the prolonged/dose‐adjusted sitagliptin treatment group. Conclusions and Implications: In rats with renal IRI, DPP4 inhibition did not alter plasma cystatin C, a marker of glomerular function, but may protect against tubular damage.